Intelligent structure prediction and visualization analysis of non-coding RNA in osteosarcoma research - Chen, Longhao; He, Liuji; Liu, Baijie; Zhou, Yinghua; Lv, Lijiang; Wang, Zhiguang (Frontiers in Oncology, 2024)
Abstract Background: Osteosarcoma (OS) is the most common bone malignant tumor in children and adolescents. Recent research indicates that non-coding RNAs (ncRNAs) have been associated with OS occurrence and development, with significant progress made in this field. However, there is no intelligent structure prediction and literature visualization analysis in this research field. From the perspective of intelligent knowledge structure construction and bibliometrics, this study will comprehensively review the role of countries, institutions, journals, authors, literature citation relationships and subject keywords in the field of ncRNAs in OS. Based on this analysis, we will systematically analyze the characteristics of the knowledge structure of ncRNAs in OS disease research and identify the current research hotspots and trends. Methods: The Web of Science Core Collection (WoSCC) database was searched for articles on ncRNAs in OS between 2001 and 2023. This bibliometric analysis was performed using VOSviewers, CiteSpace, and Pajek. Results: This study involved 15,631 authors from 2,631 institutions across 57 countries/regions, with a total of 3,642 papers published in 553 academic journals. China has the highest number of published papers in this research field. The main research institutions include Nanjing Medical University , Shanghai Jiao Tong University, Zhengzhou University, and China Medical University . Oncology Letters, European Review for Medical Pharmacological Sciences, and Molecular Medicine Reports are the most popular journals in this field, with Oncotarget being the most co-cited journal. Wei Wang, Wei Liu, and Zhenfeng Duan published the most papers, with Wang Y being the most co-cited author. “miRNA”, “lncRNA” and “circRNA” are the main focuses of ncRNAs in OS studies. Key themes include “migration and invasion”, “apoptosis and proliferation”, “prognosis”, “biomarkers” and “chemoresistance”. Since 2020, hotspots and trends in ncRNA research in OS include “tumor microenvironment”, “immune” and “exosome”. Conclusions: This study represents the first comprehensive bibliometric analysis of the knowledge structure and development of ncRNAs in OS. These findings highlight current research hotspots and frontier directions, offering valuable insights for future studies on the role of ncRNAs in OS.